A Sustainability Planning Framework and Methods for Rural Drinking Water in Satara District, Maharashtra, India - Wescoat, James L.; Murty, Jonnalagadda V. R.; Singh, Ranu; Verma, Piyush (Frontiers in Water, 2022)
Districts across India are progressing toward the national Jal Jeevan Mission goal of piped water supply and 100% Functional Household Tap Connections (FHTC) for all by 2024. While state and national data monitor progress toward tap water connection coverage, the functionality and sustainability of those piped water supplies are less clear. This study presents a Sustainability Planning Framework to assess rural drinking water conditions and needs at the village, block, and district scales. It employs a mobile app to survey five key aspects of sustainability: source water sustainability, water service sustainability, operations and maintenance financial sustainability, village institutional capacity, and asset management. Ordinal scores for these sustainability variables are analyzed and interpreted though GIS mapping to identify locations and types of village support needed. Scores are aggregated to create an overall village drinking water sustainability index. Important hydroclimatic, geomorphological, and socio-economic correlates of the drinking water sustainability index are also examined. This framework and methods can help districts in Maharashtra and other states analyze drinking water services, plan future investments, and make policy adjustments to ensure sustainability.